Pierre Bourdieu's Concepts of Habitus and Cultural Capital: Mechanisms of Intergenerational Social Inequality Reproduction (International Journal of Economics Management and Social Science, 2026)
Background: Social inequality is not merely reproduced through the direct transmission of economic resources across generations; it is also perpetuated through subtle mechanisms of cultural transmission that operate through the socialization of dispositions, tastes, and competencies valued in dominant social fields. Pierre Bourdieu's theoretical framework—centering on the concepts of habitus, field, and capital—provides the most influential sociological account of these mechanisms. Objective: This study analyzes Bourdieu's concepts of habitus and cultural capital as mechanisms of intergenerational social inequality reproduction, examining their theoretical foundations, empirical applications, and contemporary relevance. Methods: A systematic literature review was conducted using Scopus, Web of Science, and Google Scholar, covering peer-reviewed publications from 2019 to 2025 on Bourdieu's sociology, cultural reproduction, educational inequality, social stratification, and class analysis. Results: The findings confirm that habitus and cultural capital operate as powerful mechanisms of inequality reproduction in educational systems, labor markets, and cultural fields, with effects that are resistant to formal policies of equality of opportunity precisely because they operate below the threshold of conscious recognition. Conclusion: Bourdieu's framework remains indispensable for understanding the persistence of social inequality across generations, but requires critical extension to account for intersecting axes of race, gender, and digital capital, and for the agency of dominated classes in challenging cultural reproduction.Keywords: Bourdieu, habitus, cultural capital, social reproduction, intergenerational inequality, field theory, educational inequality